Pengaruh Fraksi Volume Terhadap Kekuatan Tarik Pada Serat Resam Menggunakan Resin Polyester BQTN-EX - prasetyo, Iksan; Juanda, Juanda; Rollastin, Boy (Politeknik Manufaktur Negeri Bangka Belitung, 2023)
Along with the times, the technology of utilizing natural fiber composite materials has developed, including in the field of engineering materials. One of them is natural fiber. This resam plant is easy to get because it is used in almost all corners of Indonesia, including the Bangka Belitung province because it is easy to process, and has stem content and stem size. The purpose of this study was to determine the best value for the effect of volume fraction on the tensile test of resam fiber composite materials. This study used a volume fraction variant of 10%, 15% and 20% by immersion in NaOH for 30, 60 and 90 minutes. The highest average results were obtained from the tensile test obtained from the 15% volume fraction with 60 minutes of NaOH immersion and the lowest average values were obtained from the 15% volume fraction with 90 minutes of NaOH immersion. From the research results obtained, it was concluded that the average value and variance of the tensile strength of resam fiber was found at the level 2 immersion time factor, which was for 60 minutes and the level 2 volume fraction factor, which was 15%. volume fraction, the most optimal.